2015
DOI: 10.1164/rccm.201503-0535oc
|View full text |Cite
|
Sign up to set email alerts
|

Bedside Assessment of Quadriceps Muscle by Ultrasound after Admission for Acute Exacerbations of Chronic Respiratory Disease

Abstract: Rationale: Hospitalization represents a major event for the patient with chronic respiratory disease. There is a high risk of readmission, which over the longer term may be related more closely to the underlying condition of the patient, such as skeletal muscle dysfunction. Objectives:We assessed the risk of hospital readmission at 1 year, including measures of lower limb muscle as part of a larger clinical trial. Conclusions: Smaller quadriceps muscle size, as measured by ultrasound in the acute care setting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 30 publications
(27 reference statements)
4
88
1
Order By: Relevance
“…Furthermore, among those with COPD, higher levels of systemic inflammation biomarkers are associated with poorer physical function, exacerbations, and death (46,(49)(50)(51). Sarcopenia and cachexia are more common in patients with COPD than in matched healthy control subjects and are independently associated with reduced exercise capacity, functional performance, health status, readmission following hospitalization for acute exacerbation, and mortality (17,46,(52)(53)(54). In addition, adults with COPD exhibit skeletal muscle dysfunction at the biochemical, cellular, and structural levels (13,(55)(56)(57).…”
Section: Frailty In Pulmonary Diseasementioning
confidence: 99%
“…Furthermore, among those with COPD, higher levels of systemic inflammation biomarkers are associated with poorer physical function, exacerbations, and death (46,(49)(50)(51). Sarcopenia and cachexia are more common in patients with COPD than in matched healthy control subjects and are independently associated with reduced exercise capacity, functional performance, health status, readmission following hospitalization for acute exacerbation, and mortality (17,46,(52)(53)(54). In addition, adults with COPD exhibit skeletal muscle dysfunction at the biochemical, cellular, and structural levels (13,(55)(56)(57).…”
Section: Frailty In Pulmonary Diseasementioning
confidence: 99%
“…This global measure of frailty shows the effects of COPD on the whole system. These two measures, and others recently described,78 show that identification of individuals at risk of hospital readmission or death following hospitalisation may be a realistic prospect, allowing for targeted intervention.…”
Section: Introductionmentioning
confidence: 80%
“…One recent study showed that patients admitted for COPD exacerbations with smaller quadriceps size are at increased risk for readmission and death. 31 …”
Section: How Can Bedside Ultrasonography Be Used For Screening and Rimentioning
confidence: 99%